Self efficacy, perceptions of social context, job satisfaction and their relationship with absence from work. An integrated model founded on social cognitive theory - Di Tecco, Cristina; Borgogni, Laura (La Medicina del Lavoro, 2014)
Background: Absenteeism is a major concern for organizations and companies since it has negative repercussions on productivity and represents a huge cost due to sick pay and expensive temporary replacement of employees who are obliged to take long-term absences. Objectives: The current study aimed at focussing on absenteeism and its causes through the investigation of a conceptual model founded on social cognitive theory where self-efficacy and Perceptions of Social Context (PoSC, i.e., perceptions of immediate supervisor, colleagues and top management) concur to predict absence from work through the mediating role of job satisfaction. Methods: A group of 361 sales assistants and administrative staff employed by the Italian branch of a retail clothing multinational were administered a self-report questionnaire for measuring self-efficacy, PoSC and job satisfaction. We then matched the self-report answers with objective absence measures. Results: Structural equation modelling lent support to the presumed relationships between variables. We found that: 1) self-efficacy was positively related to the three PoSC; 2) PoSC had a positive relationship with job satisfaction; 3) job satisfaction was negatively related to absence from work; 4) job satisfaction mediated the relationship between PoSC and absence from work. Conclusions: Overall, our contribution offers a theoretical basis for further investigations on the role of individual characteristics and perceptions of social context in absenteeism studies via both observational and intervention studies and cost-effectiveness analysis.